Organized Marketing and Product Design Training for Flower Cracker Producers in Sidoarjo post Covid-19 - Imani, Safarinda (Entrepreneurship and Community Development, 2023)
MSMEs in Sidoarjo that experienced the greatest impact of Covid-19 were the food or beverage sector due to declining consumer purchasing power. This analysis is significant with one of the Ngelom villages in Sidoarjo district, where MSMEs must be better known to many people. The type of business in Ngelom village is raw cracker food in the shape of a unique flower; besides that, it has the high creative power to produce this product, which can compete with other MSMEs. Hence, the a need for synergy with practitioners to organize marketing training and product design for flower cracker producers so that they can be recognized by the wider community with the unique characteristics of flower crackers with high selling power. From the results of the training, flower cracker producers themselves now have initiatives regarding packaging and marketing methods by way of us providing socialization about the use of social media and direct marketing. In addition, the product is attractive to buy and creates an aesthetic impression with a high selling price. We assist in making packaging using the Corel Draw software application. Thus, it can help improve the economy of flower cracker producers in Sidoarjo after Covid-19